The Dose Modulates the Body’s Physiology: Literature Review - Yilkal, Tariku Belay (In-Vitro-In-Vivo-In-Silico Journal, 2025)
The body interacts with endogenous and exogenous molecules through various receptor networks at the cellular and organismal levels by which the different physiological processes of the organ systems get activated. Life could no longer exist without the body’s interaction with these signaling molecules. The number of molecules interacted with a receptor type within the body determines the efficiency of biological processes that would determine the biochemistry and anatomy behind the basic body functions. The dose plays a complex role in multiple physiological processes by modulating the natural processes of the different biological systems. It is always connected to the physiological and anatomical aspects of the biological sciences in which it manifests the biological sensitivity that would determine the efficiency of biological responses of the body systems. There are always physiologic and non-physiologic doses for every compound administered into the biological systems. The does that facilitated the body to manifest that biological sensitivity which has maintained the physiological processes of the body systems was noted as physiologic dose, whereas the dose that has suppressed the biological sensitivity of the body that became inefficient in maintaining the physiological processes of the different biological systems was termed non-physiologic dose. It is important to adjust the dose or dosage based on physical and biological factors such as the efficiency of the different organ systems, body weight, and the timing of the dose triggering a biological response to maintain the natural processes of the body systems. This means that integrated biological data is required in order to be able to identify the physiologic and non physiologic doses for biological or pharmacological use.
Keywords: Dose; Signaling molecules; Physiologic; Non physiologic; modulate; Physiology